2019
DOI: 10.1029/2019ms001727
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Variable Land‐Atmosphere Coupling on Convective Cloud Populations Observed During the 2016 HI‐SCALE Field Campaign

Abstract: We use a large‐eddy simulation model with a nested domain configuration (297 and 120 km wide) and an interactive land surface parameterization to simulate the complex population of shallow clouds observed on 30 August 2016 during the Holistic Interactions of Shallow Clouds, Aerosols, and Land‐Ecosystems campaign conducted in north‐central Oklahoma. Shallow convective clouds first formed over southeast Oklahoma and then spread toward the northwest into southern Kansas. By the early afternoon, the relatively uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(78 citation statements)
references
References 93 publications
(113 reference statements)
6
72
0
Order By: Relevance
“…However, those small patches, along with water grids, suggest the water grid cells tend to delay convection. Fast, Berg, Feng, et al (2019) also observed that lakes and their downwind regions are virtually "cloud-free." Cluster analysis confirms this finding.…”
Section: 1029/2020jd032550mentioning
confidence: 96%
See 4 more Smart Citations
“…However, those small patches, along with water grids, suggest the water grid cells tend to delay convection. Fast, Berg, Feng, et al (2019) also observed that lakes and their downwind regions are virtually "cloud-free." Cluster analysis confirms this finding.…”
Section: 1029/2020jd032550mentioning
confidence: 96%
“…To isolate the effects of these factors, a sensitivity simulation is designed where large-scale winds and advection of heat and moisture are removed by forcing horizontal winds to be zero and homogenizing thermal and water vapor fields in the initial and lateral boundary conditions. The sensitivity simulation with isolated local effects is first compared with the realistic simulation discussed in Fast, Berg, Feng, et al (2019) to illustrate the comparative roles of both local and large-scale effects in cloud populations and land-atmosphere interactions. Then, the detailed characteristics of land-atmospheric interaction under the idealized conditions of no advection are investigated using a cluster analysis approach.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 99%
See 3 more Smart Citations